Towards a new ecology of shared living. Technological greenery and the Internet of Nature - Oscar Eugenio Bellini; Giuseppe Ruscica; Vittorio Paris (Agathón)
The need to create eco-friendly architecture is increasingly pushing designers to uncritically integrate greenery into shared living without considering the importance of bottom-up user involvement. The combination of Internet of Things systems and digitalisation with the benefits naturally generated by greenery could, on the contrary, promote conscious and proactive participation, including in terms of its maintenance and management. The present study recalls the advantages of the hybridization between shared living and nature and proposes an articulated taxonomy of the reversed spatial environments that can be managed through an innovative Internet of Nature system, arguing how vegetation and sensors can support the ‘ecological challenge for change’, promote the construction of a renewed social identity and strengthen a sense of belonging.